FERTILIZACIÓN CON FÓSFORO Y CONTROL DE MALEZAS PARA EL ESTABLECIMIENTO DE Brachiaria brizantha A ESCALA COMERCIAL - Ara G., Miguel (2004)
Lack of large sized suitable demonstration trials has prevented the adoption of improved pasture establishment technology at farm level in Ucayali. The aim of this experiment was to demonstrate the benefits of the mechanized pasture seeding and, particularly, the need for P fertilization and chemical weed control. The effect of three establishment treatments were evaluated using commercial size land areas. The treatments were: (A) conventional mechanized establishment, (B) conventional mechanized establishment plus P fertilization and (C) conventional mechanized establishment plus P fertilization plus chemical weed control, on seedling emergence, height and cover growth and dry biomass accumulation of a Brachiaria brizantha - Centrosema macrocarpum pasture. Unexpectedly, the effects of P fertilization and control weed with glyphosate were non significant, yet, in some cases, treatment (C) performed poorer. Seedling emergence for all treatments was notably poor, probably due to a low quality seed, insect carrying or runoff losses. Even though, the B. brizantha - C. macrocarpum pasture accumulated dry biomass representing 30% of the total vegetation in a 189 day period.